2011
DOI: 10.3354/ame01515
|View full text |Cite
|
Sign up to set email alerts
|

Response of heterotrophic stream biofilm ­communities to a gradient of resources

Abstract: The metabolism and biogeochemical cycles of aquatic ecosystems are largely mediated by microbial communities, with biofilm assemblages dominating in stream ecosystems. To determine the effects of the availability of resources on the structure and function of heterotrophic stream biofilms, we created an enrichment gradient by amending darkened stream channel mesocosms with a stoichiometrically balanced solution of sucrose, NO 3 -and PO 4 3-. A total of 1902 bacterial partial 16S rRNA gene sequences yielded 293 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 89 publications
3
25
0
Order By: Relevance
“…In contrast, the molar N/C ratio of biofilms was not related to nitrate of surface water, and the values were below the Redfield ration of 16 at all sampling sites except one. Nutrient limitation of biofilms was observed in other streams as well: Nutrient enrichment increased biomass and activity of biofilms (Van Horn et al 2011), and biofilms in North American streams were limited by phosphorus (Lehto and Hill 2013). Bechtold et al (2012) observed that streambed chlorophyll was limited by nitrate, suppressed by labile DOC, and increased with agricultural land use.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, the molar N/C ratio of biofilms was not related to nitrate of surface water, and the values were below the Redfield ration of 16 at all sampling sites except one. Nutrient limitation of biofilms was observed in other streams as well: Nutrient enrichment increased biomass and activity of biofilms (Van Horn et al 2011), and biofilms in North American streams were limited by phosphorus (Lehto and Hill 2013). Bechtold et al (2012) observed that streambed chlorophyll was limited by nitrate, suppressed by labile DOC, and increased with agricultural land use.…”
Section: Discussionmentioning
confidence: 93%
“…The variable nutrient-to-carbon stoichiometry in the quantitative most important biofilm groups (i.e., bacteria and algae) imply that limitation in essential nutrients might lower the contribution of those nutrients in the biofilms. Nutrient limitation is common in stream biofilms as demonstrated in several experiments (Van Horn et al 2011;Bechtold et al 2012;Lehto and Hill 2013).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, one study described biofilm communities with functional plasticity in groundwater-fed streams that may resist environmental fluctuations by adapting their enzymatic machinery, whereas biofilms in glacier-fed streams lacked this plasticity and were instead characterized by specialists able to express specific extracellular enzymes under given conditions Nutrients. Biogeochemical cycling in stream biofilms is not solely related to light but also to nutrient availability 86,87,88 , which is often increased by agricultural land use. The degradation of complex macromolecules by extracellular enzymes can constitute up to 80% of the microbial activity in biofilms 7 , and these enzymes are therefore fundamental to biogeochemical fluxes of carbon, nitrogen and phosphorous in streams 86,89 .…”
mentioning
confidence: 99%
“…Biogeochemical cycling in stream biofilms is not solely related to light but also to nutrient availability 86,87,88 , which is often increased by agricultural land use. The degradation of complex macromolecules by extracellular enzymes can constitute up to 80% of the microbial activity in biofilms 7 , and these enzymes are therefore fundamental to biogeochemical fluxes of carbon, nitrogen and phosphorous in streams 86,89 . The stoichiometry of biosynthetic enzymes that metabolize each of these nutrients relates to the stoichiometry of the respective nutrient in the microbial biomass, as well as to the stoichiometry of organic matter cycling.…”
mentioning
confidence: 99%
“…Experiments have been done to test effects of elevated nutrient concentration on microbial diversity, but their results differ. A clear shift in bacterial assemblage composition toward dominance of certain taxa caused a decrease in biofilm diversity after dissolved nutrient concentrations were doubled (Van Horn et al 2011). Added nutrients can also influence fungal diversity (Gulis and Suberkropp 2003).…”
Section: Stream Microbial Ecologymentioning
confidence: 99%